Comparison of Visual Field Progression in Patients with Primary Open Angle Glaucoma and Pseudo Exfoliative Glaucoma - Khaleel, Asfa; SV, Madhavi Gupta (International Journal of Clinical and Experimental Ophthalmology, 2025)
Objective: Comparison of visual field progression in patients with Primary Open-angle Glaucoma (POAG) and Pseudo Exfoliative Glaucoma (PEXG). Methods and materials: This is a 2-year longitudinal prospective study including 60 glaucomatous eyes with VA CF ≥ 3 m, IOP ≥ 20 mmHg, CDR ≥ 0.6 and those with Shaffer’s grade 3 or above were categorized as POAG along with signs of Pseudo exfoliative material as PEXG. Patients on anti-glaucoma medications and those who have undergone cataract and glaucoma surgeries are also included in this study. 24-2 visual field test was performed using Humphrey Field Analyzer & the progression was assessed based on 3 parameters- Mean Deviation (MD), Visual Field Index (VFI) & Guided Progression Analysis (GPA). Results: The difference in MD & VFI was higher in PEXG (-5.77 dB) (10.88%) than in POAG (-1.56 dB) (7.17%) respectively & was significant statistically (t - test, p = < 0.001). The GPA showed fast progression in 53.30% of cases in PEXG, 13.30% in POAG (Chi-square, p = < 0.001) about 63.30% of POAG & 46.70% of PEXG showed slow- moderate progression, but 23.30% of POAG subjects had no progression. Conclusion: Compared to POAG, the study showed that PEXG had frequent & faster visual field worsening. Therefore, PEXG patients require more stringent management & treatment than those with POAG.